Marketing Magic or Just Hype? The AI Factor in Indonesia’s MSME Growth - Johni Eka Putra; Lili Adi Wibowo; Siska Armawati Sufa; Nindi Aristi; Irzameingindra Putri Radjamin (Faculty of Law, Universitas Pekalongan, 2025)
This research investigates the strategic influence of artificial intelligence (AI) adoption on the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, emphasizing the mediating role of innovation diffusion. By synthesizing the Technology Acceptance Model (TAM), the Diffusion of Innovations (DOI) theory, and the Resource-Based View (RBV), the study analyzes how perceived usefulness and ease of use contribute to the attainment of sustained competitive advantage. Employing a quantitative methodology, the analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) on data collected from 160 MSMEs. The measurement model demonstrated strong reliability and validity. The findings reveal that technology adoption exerts a significant effect on both innovation and competitiveness, with innovation serving as a partial mediator. The R² and Q² values reflect moderate explanatory and predictive capacity. This study provides both theoretical contributions and practical recommendations for fostering digital transformation in the MSME sector through AI-driven innovation.